2020
DOI: 10.1002/essoar.10504517.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Upper-atmosphere mass density variations from CASSIOPE precise orbits

Abstract: Low Earth Orbit (LEO) satellites are significantly affected by variable air drag forces, which are mainly altered by atmospheric expansion/contraction driven by solar and geomagnetic activity. Air drag reduces the orbital velocity of a satellite, its nominal altitude, and shortens its lifespan. The effect of air drag pressure on the position of a satellite orbiting at an altitude of around 450 km may drag around 3 m per revolution in the along-track axis, limiting the satellite's lifespan to approximately 5-10… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In this study, the analysis of differences with the HASDM database have shown that scaling the CASSIOPE's drag coefficient of Calabia and Jin (2021a) by approximately 0.8 would provide a better match. Using this, the estimated altitude dependence on this scaling factor is given in Table 1.…”
Section: Results and Analysismentioning
confidence: 85%
See 4 more Smart Citations
“…In this study, the analysis of differences with the HASDM database have shown that scaling the CASSIOPE's drag coefficient of Calabia and Jin (2021a) by approximately 0.8 would provide a better match. Using this, the estimated altitude dependence on this scaling factor is given in Table 1.…”
Section: Results and Analysismentioning
confidence: 85%
“…These differences are mostly caused by inaccuracies in the models during geomagnetic storms. A deeper analysis for this particular storm can be found in Calabia and Jin (2021a).…”
Section: Results and Analysismentioning
confidence: 98%
See 3 more Smart Citations